TAGANA RAJAWALI : Peran Gereja dalam Membangun Kesiapan Bencana - Ronripiz Imanuel Rahanra; Ermin Hidayati; Roy Pieter; Josiharu Edmund Here (STT Kingdom, 2022)
Natural or non-natural disasters are an unavoidable part of human life. The impact it causes is not only physical, but also psychological. In this case, the church is challenged not only to contribute to providing a theological framework for disasters but also to be inactive and relevant to disaster victims. The purpose of this research is to photograph the role of the church, especially Tagana Rajawali, as a concrete form to build the readiness of church members to face disasters. The results of this study indicate that through Tagana Rajawali, the role of the church, both post-disaster and pre-disaster, has a very positive impact on both the surrounding community and the Indonesian nation